Primary Mucosa-Associated Lymphoid Tissue Lymphoma of the Rectum - Shapour Omidvari (Shiraz University of Medical Sciences, 2013)
Introduction Mucosa-associated lymphoid tissue (MALT) lymphoma most commonly involves the stomach and its treatment is surgery, antibiotic therapy or radiotherapy. Rectal MALT is not only so rare but treatment is not as clear as gastric MALT. Case Presentation Our patient was a 66 year-old man presenting with 5-6 months abdominal pain and anemia. In colonoscopy, a rectal ulcer was found and biopsy revealed MALT lymphoma. Physical examination and staging evaluations were normal. Radiotherapy was started for him but he did not tolerate radiotherapy and instead received chemotherapy. After 38 months, he is fine. Conclusions The incidence of rectal MALT is rare and treatment is not so clear. The results on H. pylori eradication, radiotherapy and chemotherapy are more controversial.